Beckett’s Politics of Space - Richards, Shaun (Hungarian Journal of English and American Studies, 2022)
Book review:Little, James. Samuel Beckett in Confinement: The Politics of Closed Space. London: Bloomsbury, 2020. 235 pages. ISBN 978-1-3501-123-2. Hb. $115.